Antibiotic resistance pattern in patients with urinary tract infection: an observational study - Mallam, Rupa Devi; P., Usha Kiran (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Urinary tract infection (UTI) is one of the most common diseases caused by bacteria in communities and hospital settings. With the irrational prescription of antibiotics and their misuse leads to constant increase in resistance. This study aims to evaluate the spectrum and antibiotic resistance pattern of uropathogens and to provide a basis for appropriate antimicrobial therapy in patients with UTI. Methods: A retrospective observational study was carried out for a period of 6 months from April 2018 to September 2018 at general hospital Kakinada. Data of 282 positive urine culture reports and their antibiotic susceptibility test results were collected from the records of the Microbiology department and were analyzed and depicted in percentages. Sample processing, identification of organisms, and pattern of antimicrobial sensitivity were carried out as per the Clinical and Laboratory Standards Institute guidelines. Results: Out of 282 positive reports, Escherichia coli was the most common isolated uropathogen with a total of 148 (52.4%) followed by Klebsiella 72 (26%), 20 (7.9%) each of Citrobacter and pseudomonas aeruginosa. E. coli were resistant to nalidixic acid (59.5%), cotrimoxazole (58.1%), ciprofloxacin (54%) amoxyclav (52.7%), ampicilin (45.9%), cefatoxime (37.8%), cefaperazone and salbactum (25.3%). Klebsiella were resistant to amoxyclav (77.7%), cotrimazole (50%), nalidixic acid (41.6%), ampicilin (44.4%), cefatoxime (27.7%), ciprofloxacin (25%). E. coli and Klebsiella were highly susceptible to nitrofurantoin, cefaperazone and salbactum, piperacillin and tazobactum, amikacin, imipenem, gentamicin. Conclusions: The majority of the isolated bacteria were resistant to many antibiotics commonly used in clinical practices. So prior culture reports and institutional antibiograms are necessary for prescribing antibiotics rationally.